Sustainable marketing in environmental services: a strategic case study of Alam Flora Environmental Solutions (AFES) - Abdul Hamid, Siti Ruzana; Suib, Fatin Husna; Zamuel, Aysha; Shofi, Khadijah; Muhamadtahed, Walinda; Ahmed, Sana; Awaekuechi, Nuraymee; Abdul Karim, Nurul Akmar (IIUM Press, 2025)
Alam Flora Environmental Solutions (AFES), a subsidiary of Alam Flora Sdn. Bhd. under Malakoff Corporation Berhad, is a leading Malaysian provider of integrated waste management, facility management, and sustainability solutions. Operating within the B2B sector, AFES adopts a hybrid marketing strategy that integrates digital platforms such as TikTok, Instagram, Facebook, and LinkedIn with on-ground initiatives including corporate networking events, public exhibitions, and educational outreach. This case study examines three core marketing initiatives: the “Scan and Score” and “WOW Box” programmes, which incentivise recycling through PETRONAS Mesra reward points, and strategic ESG-driven collaborations with corporations such as FMCG sectors, malls, financial institutions and many more. These initiatives collectively enhance AFES’s market positioning and support national environmental objectives. However, limitations remain in the company’s campaign evaluation process, which currently relies on basic enquiry tracking and general feedback rather than advanced analytics. To address this gap, the study recommends the integration of digital performance tools such as Google Analytics and CRM systems to enable data-driven decision-making. The findings underscore the importance of aligning innovative marketing tactics with sustainability goals and offer practical insights for environmental service providers seeking to strengthen competitive advantage through strategic, adaptive marketing.